Lithospheric S Wave Velocity Variations Beneath the Mackenzie Mountains and Northern Canadian Cordillera. Issue 1 (28th December 2022) - Schutt, Derek L.; Porritt, Robert W.; Estève, Clément; Audet, Pascal; Gosselin, Jeremy M.; Schaeffer, Andrew J.; Aster, Richard C.; Freymueller, Jeffrey T.; Cubley, Joel F.
Abstract: The Mackenzie Mountains (MMs) in the Yukon and Northwest Territories, Canada, are an enigmatic mountain range. They are currently uplifting (Leonard et al., 2008, https//doi.org/10.1029/2007JB005456 ), yet are about 700 km from the nearest plate boundary. Their arcuate shape is distinct and extends over 100 km eastward from the general trend of the Northern Canadian Cordillera. To better assess the cause and conditions of the current uplift, we processed ambient seismic noise data from a linear array of broadband seismographs crossing the mountains, along with other regional seismic stations, to estimate Rayleigh wave phase velocities between 6 and 40 s periods. From this, we estimated phase velocity dispersion and performed a tomographic inversion to estimate V S . Tomography reveals a low‐velocity structure that extends upward from the base of the ∼50–66 km thick lithosphere to the upper crust, and we hypothesize that inferred low density and low rigidity associated with the V S anomaly localizes the ongoing uplift and thrust‐dominated seismicity of the MMs. Additionally, we find relatively low crustal velocities that extend to the west of the MMs, suggesting that strain transfer from the Gulf of Alaska plate boundary plays a driving role as the crust translates to the northeast and buckles up against the craton consistent with the orogenic float hypothesis of Mazzotti and Hyndman (2002, https//doi.org/10.1130/0091-7613(2002)030〈0495:YCASTA〉2.0.CO;2 ). Finally, we observe lithospheric azimuthal anisotropy with an NW‐SE fast direction. This is nearly orthogonal to teleseismic shear wave splitting measurements in the central MMs, and suggests that asthenosphere flow and lithospheric strain are not aligned in this region. Plain Language Summary: The Mackenzie Mountains (MMs) in the Yukon and Northwest Territories of NW Canada are actively uplifting, but lie approximately 700 km east of the nearest plate boundary where primary forces that cause mountain uplift are expected to originate. To investigate why these mountains are currently rising, we processed background seismic noise to extract fundamental mode seismic surface (Raleigh) wave phase velocities for raypaths between pairs of seismographs. We inverted these data to shear wave velocity to obtain a 3‐D image of seismic shear wave velocity, which is sensitive to the rigidity, and thus the strength, of the crust and uppermost mantle. We find a notable volume of low shear wave velocities beneath the highest extent of the mountains that extends from the upper crust (several km depth) to near the bottom of the tectonic plate (around 50–66 km depth). We conjecture that this compositional, thermal, and/or fluid‐based anomaly is intimately related to current uplift and its unusual location east of the general Cordillera in that its weak nature focuses deformation and uplift in the MMs. Key Points: We image an 5% reduction in VS beneath the highest extent of the Mackenzie Mountains that extends from the asthenosphere to the upper crust Lithospheric VS anisotropy shows a dominant NW‐SE fast orientation and contrasts with bulk upper mantle SKS splitting results VS shows marked heterogeneity including a low‐velocity lower‐crustal channel west of the Cordilleran Deformation Front